Method for synthesizing nano zero-valent iron by taking tetrahydrofuran as reaction medium to improve oxygen activation efficiency and application of nano zero-valent iron
By using tetrahydrofuran as the reaction medium and Fe2+ coordination agent in the synthesis of nano zero-valent iron, a controllable nZVI-THF was formed and encapsulated by SiO2, the problem of insufficient ROS generation in tumor treatment was solved. , significantly improves the oxygen activation efficiency and electron contribution rate, achieves efficient ROS generation in tumor cells, and promotes tumor cell death.
Patent Information
- Application Number
- CN202411390325.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-10-08
AI Technical Summary
The application of existing nano zero-valent iron (nZVI) in tumor treatment is limited by its easy agglomeration, low electron contribution rate and low oxygen molecule activation efficiency, which leads to insufficient ROS generation, hindering its application in the field of tumor treatment. .
Tetrahydrofuran (THF) is used as the reaction medium, coordinated with Fe2+ in liquid phase reduction method, synthesize controllable nano zero-valent iron (nZVI-THF), and encapsulate it through disulfide bond-containing SiO2 to improve its biological function. Compatibility and ROS generation capability.
It significantly improves the electron contribution rate and oxygen activation efficiency of nZVI, enhances the ROS generation ability, and can induce oxygen activation in tumor cells to produce high levels of reactive oxygen species, effectively promoting the death of tumor cells.
Smart Images

Figure CN119235913A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biomedicine, and specifically relates to a method for synthesizing nanometer zero-valent iron using tetrahydrofuran as a reaction medium to improve oxygen activation efficiency and an application thereof. Background Art
[0002] Usually, tumor treatment is often accompanied by the introduction of external energy, such as photodynamic therapy (PDT), magnetic hyperthermia therapy (MHT), etc., which increases the complexity of the operation and the severity of the treatment conditions. In recent years, studies have found that nano zero-valent iron (nZVI) has a strong reducing property (E θ (Fe 2+ / Fe 0 )=-0.44V), it is widely used as an electron donor in the field of water organic pollutant treatment. Among them, nZVI is used as an electron donor to activate molecular oxygen to produce H2O2 and Fe through a double electron transfer pathway. 2+ (Equation 1). At the same time, molecular oxygen reacts with the in-situ generated Fe 2+ The reaction generates O2 - (Equation 2), with higher activity·O2 - Continue with Fe 2+ The reaction generates H2O2 (Equation 3), which can be further reduced to highly reactive ·OH (Equation 4). However, nZVI is usually prone to agglomeration and the electron contribution rate of nZVI is limited, resulting in a very limited yield of ROS, which seriously hinders the application of nZVI in the field of tumor treatment.
[0003] O2+Fe 0 +2H + →Fe 2+ +H2O2 (1)
[0004] O2+Fe 2+ → O2 - +Fe 3+ (2)
[0005] O2 - +2H + +Fe 2+ →H2O2+Fe 3+ (3)
[0006] H2O2+e - → OH+OH - (4)
[0007] As we all know, the synthesis and preparation of nZVI has long been a hot topic in the field of nanotechnology. Traditionally, the synthesis and preparation of nZVI are often limited by the complex operation process, unstable product performance, uncontrollable nanoparticle morphology and Fe 0 For example, the mechanical ball milling method has high energy consumption and the professional equipment is expensive; the thermal decomposition method of the organometallic precursor has unstable reaction process and often contains organic impurities. Although the classic liquid phase reduction method has advantages such as simple operating conditions and controllable product morphology, the prepared nZVI is easily oxidized by oxygen and has disadvantages such as low electron contribution rate. At present, studies have found that some organic matter will react with Fe 2+ Coordination complexation regulates the morphology of nanoparticles during the synthesis and preparation of nZVI, making them evenly dispersed and obtaining a smaller size (about 200nm). Based on this, we introduced tetrahydrofuran (THF) and Fe in the synthesis process of nZVI using a liquid phase reduction method. 2+ The nZVI-THF with controllable morphology was prepared by coordination. At the same time, we compared the nZVI-CTAB synthesized with hexadecyltrimethylammonium bromide (CTAB) as a surfactant and found that the nZVI-THF synthesized with THF as the reaction medium has a higher electron contribution rate.
[0008] Considering that nZVI-THF prepared by liquid-phase reduction method has the characteristics of uniform nanoparticle dispersion and small particle size, high ROS production and good biocompatibility, we developed nZVI-THF-ss-SiO2 cancer therapy nanomaterials, using nZVI-CTAB-ss-SiO2 as a control material, highlighting the ROS-generating ability of nZVI-THF and the tumor cell-killing effect of nZVI-THF-ss-SiO2.
[0009] Based on the above considerations, the present invention directly introduces THF for coordination reduction during the synthesis of nZVI, and finds that THF can effectively reduce Fe 0 loss and enhance the electron contribution rate of nZVI, making Fe 0 More efficiently promotes the activation of molecular oxygen (Equation 1-4), promoting the generation of ROS. On the other hand, nZVI surface modified with CTAB cannot effectively protect Fe 0 , only a trace amount of ROS is produced. In addition, cell experiments show that the nZVI-THF-ss-SiO2 material obtained after encapsulation with disulfide bonds has excellent ROS production ability in tumor cells (HpG2 cells), which indicates that the nZVI-THF-ss-SiO2 material can be used in tumor treatment.
[0010] The inventor conducted the following search on the relevant contents of this application:
[0011] 1. Search results from http: / / scholar.glgoo.com / : (2024 / 9 / 22)
[0012] Search keywords Search Results Patented tetrahydrofuran improves the oxygen activation efficiency of nZVI 4 items, none of which are relevant to this method. Patented tetrahydrofuran enhances the electron contribution rate of nZVI 1 item, none of which are relevant to this method. Patented tetrahydrofuran synthesis of nZVI 7 items, none of which are relevant to this method. <![CDATA[Patent Tetrahydrofuran Improves the Fe 0 Content]]> 5 items, none of which are relevant to this method.
[0013] 2. CNKI search results: (2024 / 9 / 22)
[0014] Search method 1:
[0015] Title-----Tetrahydrofuran improves the oxygen activation efficiency of nZVI by 0.
[0016] Title-----Tetrahydrofuran enhances the electron contribution rate of nZVI 0 term.
[0017] Title-----Synthesis of nZVI from tetrahydrofuran 257 items, none of which are relevant to this method.
[0018] Title-----Tetrahydrofuran increases the Fe content of nZVI 0 Content 0 items.
[0019] Search method 2:
[0020] Full text -----Tetrahydrofuran improves the oxygen activation efficiency of nZVI by 336 items, none of which are related to this method.
[0021] Full text---The electron contribution rate of tetrahydrofuran to nZVI is enhanced by 1210 items, all of which are irrelevant to this method.
[0022] Full text------tetrahydrofuran synthesis nZVI123469 items, none of which are relevant to this method.
[0023] Full text-----Tetrahydrofuran increases the Fe content of nZVI 0 There are 916 contents, none of which are relevant to this method.
[0024] Search method three:
[0025] Keyword----Tetrahydrofuran 2297 items, none of which are relevant to this method.
[0026] Keyword--oxygen activation 141 items, none of which are relevant to this method.
[0027] Keyword----Nano-zero-valent iron 1388 items, none of which are relevant to this method. Summary of the invention
[0028] In view of this, the present invention provides a method for synthesizing nano zero-valent iron using tetrahydrofuran as a reaction medium to improve oxygen activation efficiency and its application. The strong reducing property of nano zero-valent iron (nZVI) enables it to act as an electron donor to activate molecular oxygen and produce a large amount of ROS. However, the conventional nZVI preparation method cannot effectively guarantee the high electron contribution rate of nZVI and the uniform dispersion and small size of the morphology, especially during the preparation process, the Fe 0 It is easy to be oxidized by O2 in the environment, so that the activation efficiency of oxygen molecules on the surface of nZVI is low and the amount of ROS generated is small in subsequent applications. The present invention compares nZVI-CTAB synthesized using hexadecyltrimethylammonium bromide (CTAB) as a surfactant with nZVI-THF synthesized using THF as a reaction medium, highlighting the feasibility of the nZVI-THF synthesis method and the higher oxygen activation efficiency of nZVI-THF.
[0029] The method of synthesizing nanometer zero-valent iron using tetrahydrofuran as a reaction medium to improve oxygen activation efficiency comprises the following steps:
[0030] Under N2 atmosphere, add 20mL of tetrahydrofuran to a conical flask (reactor); weigh 14mg of ferrous sulfate heptahydrate, add 4mL of dilute sulfuric acid solution (pH=3) to fully dissolve it, then add it to the conical flask, and disperse it evenly by ultrasonication. The solution in the flask changes from clear to yellow; weigh 0.1g of sodium borohydride, dissolve it fully with 1mL of dilute sulfuric acid solution (pH=3), and then add it dropwise to the conical flask. The reaction solution in the flask gradually changes from yellow to black. Continue ultrasonication for 80min, take out the black solution in the conical flask, immediately centrifuge and collect the precipitate, wash it with deionized water (deoxygenated) and anhydrous ethanol, and dry it in vacuo at room temperature to obtain a black nZVI-THF solid powder.
[0031] The size of the nanometer zero-valent iron material prepared by the invention is about 200nm.
[0032] Application of the nano zero-valent iron material prepared by the present invention in the preparation of tumor treatment drug preparations.
[0033] The present invention uses SiO2 containing disulfide bonds to encapsulate nZVI-THF materials, thereby improving the biocompatibility of nZVI-THF materials and the specific response of cancer cells to the materials in subsequent tumor treatment. The present invention finally determines through optimization experiments that the above parameters can ensure that a silicon dioxide outer layer with a suitable thickness is obtained after encapsulation.
[0034] The specific steps include:
[0035] First, weigh 5 mg of nZVI-THF material and DSPE-mPEG 20005 mg was added into a glass bottle, 6.35 mL of anhydrous ethanol was added into the glass bottle, and ultrasonicated for 1 min to disperse evenly.
[0036] Then, 1.35 mL of deionized water and 400 μL of ammonia water (5.38 mol / L) were added to the above glass bottle, and the mixture was dispersed evenly by ultrasonication for 1 min.
[0037] Next, 3.4 μL of tetraethyl silicate and 1.6 μL of bis-[3-(triethoxysilyl)propyl]-disulfide were added to a glass bottle, ultrasonicated for 5 min, 0.1 μL of bis-[3-(triethoxysilyl)propyl]-tetrasulfide was added, and ultrasonicated for 2 h.
[0038] Finally, after the reaction is completed, the precipitate is collected by centrifugation, washed with anhydrous ethanol, and dried under vacuum at room temperature to obtain nZVI-THF-ss-SiO2 material.
[0039] The nZVI-THF-ss-SiO2 material of the present invention can induce Fe 0 Promote the activation of molecular oxygen and produce high levels of ROS in tumor cells.
[0040] The reason why the nZVI-THF material prepared by using THF as the reaction medium has good ROS generation ability is that THF mainly improves the oxygen activation efficiency of nZVI through the following pathways:
[0041] Approach: Introducing THF during the preparation of nZVI materials can significantly increase the total number of electrons provided by nZVI-THF materials, so that more molecular oxygen on the surface of nZVI-THF materials is activated and more ROS is generated.
[0042] The nZVI-THF material has a high electron contribution rate and excellent ROS generation ability. At the same time, nZVI-THF-ss-SiO2 encapsulated with disulfide-bonded SiO2 can induce oxygen activation in cells to produce a large amount of reactive oxygen species, induce the accumulation of intracellular lipid peroxides, and effectively promote the iron death of tumor cells.
[0043] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0044] 1. The present invention adopts a liquid phase reduction method and tetrahydrofuran as a reaction medium to synthesize nZVI materials, which effectively enhances the electron contribution rate of nZVI materials and improves the activation efficiency of oxygen molecules on the surface of nZVI materials, providing a new idea for improving the oxygen activation efficiency of nZVI materials.
[0045] 2. The nZVI-THF-ss-SiO2 material described in the present invention has the potential to serve as a highly efficient ROS inducer in the tumor microenvironment. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 This is a transmission electron microscope (TEM) image of nZVI-THF and nZVI-CTAB materials. Figure 1 It can be seen that nZVI-THF has a spherical morphology, and the size of a single nanoparticle is about 200 nm; nZVI-CTAB has a spherical morphology, and the size of a single nanoparticle is about 200 nm.
[0047] Figure 2 It is the X-ray photoelectron spectrum (XPS) of nZVI-THF and nZVI-CTAB materials. Figure 2 It can be seen that the surface of ZVI-THF material has a high Fe 0 content, while it is difficult to detect Fe on the surface of nZVI-CTAB 0 The results show that the Fe 0 The content is much higher than that of Fe on the surface of nZVI-CTAB material 0 content.
[0048] Figure 3 This is the experimental result diagram of the electron contribution rate of nZVI-THF and nZVI-CTAB materials measured using a gas chromatography-thermal conductivity detector (GC-TCD) system. Figure 3 It can be seen that the hydrogen production of nZVI-THF material is significantly higher than that of nZVI-CTAB material. This result indicates that the electron contribution rate of nZVI-THF material is higher than that of nZVI-CTAB material.
[0049] Figure 4 This is a UV-visible absorption spectrum diagram using methylene blue (MB) to detect the difference in the amount of ROS generated by nZVI-THF and nZVI-CTAB materials. Figure 4 The results showed that the absorbance of MB detected in the nZVI-CTAB material experimental group decreased less, while the absorbance of MB detected in the nZVI-THF material experimental group decreased significantly under the same conditions, indicating that the nZVI-THF material can more effectively activate molecular oxygen to produce more ROS.
[0050] Figure 5 The fluorescence spectrum of nZVI-THF material producing ROS by oxygen activation is detected using DCFH-DA (2,7-dichlorofluorescein diacetate) as a probe. Figure 5It can be seen that compared with nZVI-CTAB, the fluorescence emission intensity of DCFH-DA detected in the nZVI-THF material experimental group at 530 nm is significantly increased, indicating that nZVI synthesized using THF can improve the oxygen activation efficiency of nZVI and produce more ROS.
[0051] Figure 6 This is an experimental result diagram of further evaluating the oxygen activation ability of nZVI-THF material using TPA (terephthalic acid) as an indicator. TPA will undergo an addition reaction in the presence of ·OH, and TPA will form hTPA (hydroxyterephthalate) in the molecule. hTPA is more prone to fluorescence resonance energy transfer than TPA, thereby enhancing the fluorescence signal intensity. Figure 6 It can be seen that the fluorescence signal intensity of the nZVI-THF material experimental group is the highest, about twice that of the nZVI-CTAB material experimental group. This shows that the nZVI synthesized using THF can improve the oxygen activation efficiency of nZVI and produce more ·OH.
[0052] Figure 7 The experimental results of further evaluating the oxygen activation ability of nZVI-THF material using DHR 123 (dihydrorhodamine 123) as an indicator. The molecular structure of DHR 123 contains a dichlorofluorescein group and a diacetate group. When DHR123 reacts with ·O2 - During the reaction, O2 - It is reduced to the dichlorofluorescein group of DHR 123, changing it from a non-fluorescent state to a fluorescent state. Figure 7 It can be clearly seen that the fluorescence signal intensity of the nZVI-THF material experimental group is the highest, about 3 times that of the nZVI-CTAB material experimental group. This shows that the nZVI-THF material can improve the efficiency of molecular oxygen activation and produce more O2 - .
[0053] Figure 8 This is an experimental result diagram of further exploring the oxygen activation pathway of nZVI-THF material using titanium sulfate (Ti(SO4)2) as an indicator. Figure 8 It can be clearly seen that the fluorescence signal intensity of the nZVI-THF material experimental group is the highest, about 11 times that of the nZVI-CTAB material experimental group, indicating that the nZVI-THF material can improve the efficiency of molecular oxygen activation and produce more H2O2.
[0054] Fig. 9 This is an experimental result diagram of further exploring the oxygen activation pathway of nZVI-THF material using DHR 123 (dihydrorhodamine 123) as an indicator. Fig. 9It can be clearly seen that compared with air conditions, the fluorescence signal intensity of nZVI-THF material is significantly improved under oxygen-rich conditions, indicating that the molecular oxygen activation product of nZVI-THF material exists. - This further illustrates that the pathway for nZVI-THF materials to generate ROS is through the activation of oxygen molecules.
[0055] Fig.10 This is the experimental result obtained by EPR detection using the free radical scavenger DMPO. Fig.10 It can be seen that there are obvious 1:2:2:1EPR signals of DMPO-·OH in the experimental groups containing nZVI-THF materials and nZVI-CTAB materials, indicating that the molecular oxygen activation products of the experimental groups of nZVI-THF materials and nZVI-CTAB materials exist·OH. At the same time, DMPO-·O2 - The sextet EPR signal of nZVI-CTAB material group was difficult to detect DMPO-·O2 - The sextet EPR signal indicates that the molecular oxygen activation product of nZVI-THF material exists. - However, the molecular oxygen activation ability of nZVI-CTAB material is limited, making it difficult to detect O2 by EPR. - .
[0056] Fig.11 This is an experimental result obtained by using a confocal laser scanning microscope and DCFH-DA as a fluorescent probe to monitor the content of ROS in cells. Fig.11 It can be clearly observed that compared with nZVI-CTAB-ss-SiO2, obvious green fluorescence was shown in the HpG2 cell (human liver cancer cell) experimental group treated with nZVI-THF-ss-SiO2 material, which indicates that nZVI-THF-ss-SiO2 can induce intracellular oxygen activation and produce more ROS.
[0057] Fig.12 This is a transmission electron microscope image of nZVI-THF-ss-SiO2 material after the nZVI-THF material is encapsulated by SiO2 containing disulfide bonds. Fig.12 It can be seen that nZVI-THF has a spherical morphology, the size of a single nanoparticle is about 200 nm, and there is an obvious encapsulation layer on the outside of the nanoparticle. DETAILED DESCRIPTION
[0058] The technical solution of the present invention is further analyzed and explained below through specific embodiments.
[0059] Example 1: Preparation of target product
[0060] 1. Preparation of nZVI-THF and nZVI-CTAB materials
[0061] Preparation of nZVI-THF material: Under N2 atmosphere, add 20mL of tetrahydrofuran to a conical flask (reactor); weigh 14mg of ferrous sulfate heptahydrate, add 4mL of dilute sulfuric acid solution (pH=3) to fully dissolve it, then add it to the conical flask, and disperse it evenly by ultrasonication. The solution in the flask changes from clear to yellow; weigh 0.1g of sodium borohydride, dissolve it fully with 1mL of dilute sulfuric acid solution (pH=3), and add it dropwise to the conical flask. The reaction liquid in the flask gradually changes from yellow to black. Continue ultrasonication for 80min, take out the black solution in the conical flask, immediately centrifuge and collect the precipitate, wash it with deionized water (deoxygenated) and anhydrous ethanol, and dry it in vacuo at room temperature to obtain a black nZVI-THF solid powder.
[0062] Preparation of nZVI-CTAB material: Under N2 atmosphere, add 20mL of dilute sulfuric acid solution (pH=3) to a conical flask (reactor); weigh 14mg of ferrous sulfate heptahydrate and 52.3mg of CTAB, add 4mL of dilute sulfuric acid solution (pH=3) to fully dissolve, then add to the conical flask, ultrasonically disperse evenly, and keep the solution in the flask clear; weigh 0.1g of sodium borohydride, dissolve it in 1mL of dilute sulfuric acid solution (pH=3), and add it dropwise to the conical flask. The reaction liquid in the flask gradually changes from clear to black, and a large amount of foam appears. Continue ultrasonication for 80 minutes, take out the black solution in the conical flask, immediately centrifuge and collect the precipitate, wash it with deionized water (deoxygenated) and anhydrous ethanol, and vacuum dry it at room temperature to obtain a black nZVI-CTAB solid powder.
[0063] 2. Preparation of nZVI-THF-ss-SiO2 materials and nZVI-CTAB-ss-SiO2 materials
[0064] Preparation of nZVI-THF-ss-SiO2 material: First, weigh 5 mg of nZVI-THF material and 5 mg of DSPE-mPEG 2000 Add to a glass bottle, add 6.35 mL of anhydrous ethanol to the glass bottle, and ultrasonicate for 1 min to disperse evenly.
[0065] Then, 1.35 mL of deionized water and 400 μL of ammonia water (5.38 mol / L) were added to the above glass bottle, and the mixture was dispersed evenly by ultrasonication for 1 min.
[0066] Next, 3.4 μL of tetraethyl silicate and 1.6 μL of bis-[3-(triethoxysilyl)propyl]-disulfide were added to a glass bottle, ultrasonicated for 5 min, 0.1 μL of bis-[3-(triethoxysilyl)propyl]-tetrasulfide was added, and ultrasonicated for 2 h;
[0067] Finally, after the reaction is completed, the precipitate is collected by centrifugation, washed with anhydrous ethanol, and dried in vacuum at room temperature to obtain nZVI@THF-ss-SiO2 material.
[0068] Preparation of nZVI-CTAB-ss-SiO2 material: First, weigh 5 mg of nZVI-CTAB material and 5 mg of DSPE-mPEG 2000 Add to a glass bottle, add 6.35 mL of anhydrous ethanol to the glass bottle, and ultrasonicate for 1 min to disperse evenly.
[0069] Then, 1.35 mL of deionized water and 400 μL of ammonia water (5.38 mol / L) were added to the above glass bottle, and the mixture was dispersed evenly by ultrasonication for 1 min.
[0070] Next, 3.4 μL of tetraethyl silicate and 1.6 μL of bis-[3-(triethoxysilyl)propyl]-disulfide were added to a glass bottle, ultrasonicated for 5 min, 0.1 μL of bis-[3-(triethoxysilyl)propyl]-tetrasulfide was added, and ultrasonicated for 2 h;
[0071] Finally, after the reaction is completed, the precipitate is collected by centrifugation, washed with anhydrous ethanol, and dried under vacuum at room temperature to obtain nZVI-CTAB-ss-SiO2 material.
[0072] Example 2: Investigation of the improvement of nZVI electron contribution rate using THF as the reaction medium
[0073] Determination of electron contribution rate. First, accurately measure the volume of the glass bottle, add 10 mg of sample (nZVI-THF or nZVI-CTAB) into the glass bottle, gently tilt it on one side of the glass bottle, pass N2 on the other side of the bottom of the glass bottle and keep it for 10 minutes, and immediately seal the mouth of the glass bottle with a rubber stopper. Next, add 15 mL of 2.4 moL / L HCl solution while avoiding contact with any particles. Ultrasonicate for 2 minutes to allow full contact, and let it stand for 2 hours to allow complete reaction. Finally, use a gas chromatography-thermal conductivity detector (GC-TCD) system and carrier gas (argon) to measure H2 in the headspace to calculate the nZVI electron contribution rate of each sample. Three sets of parallel experiments were performed for the determination of the nZVI electron contribution rate of nZVI-THF material and nZVI-CTAB material.
[0074] Example 3: Using THF as the reaction medium to improve the oxygen activation efficiency of nZVI and explore the oxygen activation products of nZVI-THF materials
[0075] 1. MB degradation detection of ROS generation
[0076] The nZVI-THF material (200 μg / mL) and nZVI-CTAB material (200 μg / mL) were respectively dispersed in MB (6 μg / mL) solution, ultrasonicated for 30 seconds, reacted for 30 minutes, and then centrifuged (10000 rpm, 1 minute). The supernatant was taken and the absorbance change near 660 nm was recorded by UV-visible spectroscopy to explore the degradation differences of MB solutions of nZVI-THF material and nZVI-CTAB material.
[0077] 2. ROS probe DCFH-DA detects ROS generation
[0078] First, prepare DCFH-DA (2 mM, DMSO) solution and NaOH (0.01 M) solution. Add 100 uL DCFH-DA solution and 0.8 mL NaOH solution into a 2 mL centrifuge tube and mix well. Activate at room temperature in the dark for 30 min to prepare ROS detection solution.
[0079] Next, nZVI-THF material (200 μg / mL) and nZVI-CTAB material (200 μg / mL) were dispersed in ROS detection solution (200 μL) and ultrasonicated for 30 seconds to make them fully contact. In the dark, O2 was introduced into the two reaction solutions for 15 minutes, and then centrifuged (10000 rpm, 1 minute) to take the supernatant and record the change of fluorescence intensity near 530 nm.
[0080] 3. OH probe TPA detection OH generation
[0081] First, TPA (0.5 mM) solution and NaOH (0.2 mM) solution were prepared and mixed evenly, and activated at room temperature in the dark for 30 min to prepare ·OH detection solution.
[0082] Next, nZVI-THF material (200 μg / mL) and nZVI-CTAB material (200 μg / mL) were dispersed in OH detection solution (200 μL) and ultrasonicated for 30 seconds to make them fully contact. In the dark, O2 was introduced into the two reaction solutions for 15 minutes, and then centrifuged (10000 rpm, 1 minute) to take the supernatant and record the change of fluorescence intensity near 425 nm.
[0083] 4. O2 - Probe DHR 123 detection · O2 - generate
[0084] First, prepare DHR 123 (1 mM) solution, shake it thoroughly at room temperature in the dark to mix it evenly, and prepare ·O2 - Detection fluid.
[0085] Next, nZVI-THF material (200 μg / mL) and nZVI-CTAB material (200 μg / mL) were dispersed in O2 - The detection solution (20 μL) was ultrasonicated for 30 seconds to ensure full contact. In the dark, O2 was introduced into the two reaction solutions for 15 minutes, and then centrifuged (10000 rpm, 1 minute) to take the supernatant and record the change in fluorescence intensity near 525 nm.
[0086] 5. H2O2 detector Ti(SO4)2 detects the generation of H2O2
[0087] The H2O2 concentration was determined by the titanium sulfate (Ti(SO4)2) reagent method. Titanium sulfate reagent (4 mg / mL) was prepared by dissolving titanium sulfate in sulfuric acid (ω(H2SO4)=25%). Then, 1.2 mL of nZVI-THF or nZVI-CTAB (50 mg / mL, pH=6.0) was added dropwise to 2 mL of titanium sulfate reagent at intervals of 2 minutes, 4 minutes, and 6 minutes. After adding nZVI-THF or nZVI-CTAB (50 mg / mL, pH=6.0), it was allowed to stand for 6 hours. The UV-Vis spectroscopy (λ Abs =415 nm) to measure the absorption spectrum of the yellow complex (H2[TiO2(SO4)2]).
[0088] 6. O2 - Probe DHR 123 explores the oxygen activation pathway of nZVI-THF materials
[0089] Two nZVI-THF material reaction solutions (200 μg / mL) were prepared, and DHR123 solution (10 μL / mL) was added to each of them. Air or O2 was introduced into the two reaction solutions for 15 min under light protection. The solutions were centrifuged (10,000 rpm, 1 min), and the supernatant was taken to record the change in fluorescence intensity near 525 nm to explore the electron transfer pathway during the oxygen activation process of the nZVI-THF material.
[0090] 7. Electron spin resonance spectroscopy (EPR) detection OH
[0091] Using DMPO (5,5-dimethyl-1-pyrroline-N-oxide) as a capture agent, EPR detection determined that the ROS generated by oxygen activation of nZVI-THF material were ·OH and ·O2 - , the ROS generated by oxygen activation of nZVI-CTAB material is ·OH, while ·O2 - It is difficult to detect. This indicates that the molecular oxygen activation product of nZVI-THF material exists. - , while the molecular oxygen activation of nZVI-CTAB material produces ·O2 -The production is very limited.
[0092] Example 4: Detection of intracellular ROS
[0093] DCFH-DA was used to detect the production of ROS in cells under different treatment conditions. HepG2 (37°C, 5% CO2) was cultured for 24 hours and then incubated with nZVI-THF-ss-SiO2 (300μg / mL) and nZVI@CTAB-ss-SiO2 (300μg / mL) for 16 hours, and then washed three times with PBS. Then, DCFH-DA was added and incubated for 15 minutes, and then washed three times with PBS, 1mL PBS was added, and fluorescence imaging was observed with a confocal laser scanning microscope.
Claims
1. A method for synthesizing nanometer zero-valent iron using tetrahydrofuran as a reaction medium to improve oxygen activation efficiency, characterized in that: By introducing tetrahydrofuran into the preparation process of nano zero-valent iron, tetrahydrofuran is used to regulate the morphology of nano zero-valent iron and improve Fe 0 The activation efficiency of oxygen molecules.
2. The method according to claim 1, characterized in that The steps include: Under N2 atmosphere, tetrahydrofuran was added into the reactor; ferrous sulfate heptahydrate was weighed, diluted sulfuric acid solution was added to fully dissolve it, and then added into a conical flask, and ultrasonic dispersion was performed evenly, and the solution in the flask changed from clear to yellow; sodium borohydride was weighed, diluted sulfuric acid solution was used to fully dissolve it, and then added dropwise into the conical flask, and the reaction liquid in the flask gradually changed from yellow to black, and ultrasonication was continued. The black solution in the conical flask was taken out, and the precipitate was immediately centrifuged and collected, washed with deionized water and anhydrous ethanol, and dried in vacuo at room temperature to obtain a black nZVI-THF solid powder.
3. The method according to claim 1, characterized in that: The pH of the dilute sulfuric acid solution is 3.
4. Use of the nano zero-valent iron material prepared according to claim 1, 2 or 3 in the preparation of tumor treatment drug preparations.
5. Use of the nano zero-valent iron material prepared according to claim 1, 2 or 3 in the preparation of ROS inducers.
6. The use according to claim 4, characterized in that: The nZVI-THF material is encapsulated with SiO2 containing disulfide bonds to improve the biocompatibility of the nZVI-THF material and the specific response of cancer cells to the material in subsequent tumor treatment.
7. The use according to claim 6, characterized in that The steps include: Step 1: Weigh nZVI-THF material and DSPE-mPEG 2000 Add to a glass bottle, add anhydrous ethanol to the glass bottle, and disperse evenly by ultrasonication; Step 2: Add deionized water and ammonia water into the above glass bottle and disperse evenly by ultrasonication; Step 3: Add tetraethyl silicate and bis-[3-(triethoxysilyl)propyl]-disulfide into a glass bottle, sonicate for 5 minutes, add bis-[3-(triethoxysilyl)propyl]-tetrasulfide, and react by sonication; Step 4: After the reaction is completed, centrifuge and collect the precipitate, wash it with anhydrous ethanol, and dry it under vacuum at room temperature to obtain nZVI-THF-ss-SiO2 material.
8. The use according to claim 7, characterized in that: In step 1, weigh 5 mg of nZVI-THF material and DSPE-mPEG 2000 5 mg was added into a glass bottle, 6.35 mL of anhydrous ethanol was added into the glass bottle, and ultrasonic dispersion was performed evenly.
9. The use according to claim 7, characterized in that: In step 2, 1.35 mL of deionized water and 400 μL of aqueous ammonia were added to the above glass bottle and dispersed evenly by ultrasonication.
10. The use according to claim 7, characterized in that: In step 3, 3.4 μL of tetraethyl silicate and 1.6 μL of bis-[3-(triethoxysilyl)propyl]-disulfide were added to a glass bottle, ultrasonicated for 5 min, 0.1 μL of bis-[3-(triethoxysilyl)propyl]-tetrasulfide was added, and ultrasonicated for 2 h.
Citation Information
Patent Citations
Green synthesis method for nanometer zero-valent iron by utilizing grape seeds and application thereof
CN104174870A
Method for preparing nanometer zero-valent iron on basis of liquid complexing reduction method
CN105397104A
Method for preparing zero-valent iron from iron tailings based on liquid phase reduction
CN116689773A
Method for improving oxygen activation efficiency by using metformin modified Fe < 0 > nano material
CN117816956A
Zero-valent iron, especially aged for use as an antiviral agent, a method for the preparation of zero-valent iron and zero-valent iron prepared using the method
EP4176722A1
